Disentangling depression and anxiety in relation to neuroticism, extraversion, suicide, and self‐harm among adult psychiatric inpatients with serious mental illness. (30th December 2015) - Subica, Andrew M.; Allen, Jon G.; Frueh, B. Christopher; Elhai, Jon D.; Fowler, J. Christopher
Abstract : Objectives: Little is known about depression–anxiety comorbidity and its association with personality traits and suicide/self‐harm in adult psychiatric inpatients with serious mental illness (SMI), impacting clinical assessment and treatment. This study sought to determine the symptom structure of depression–anxiety comorbidity and its relation to neuroticism, extraversion, and suicide/self‐harm behaviour in this high‐risk population. Design: Nine hundred and sixty‐two adults receiving inpatient care at a private psychiatric hospital completed questionnaires at admission. Methods: Confirmatory factor analyses compared a bifactor solution specifying a general distress factor and two specific depression and anxiety factors against unidimensional and correlated factors solutions. The bifactor solutions' factors were subsequently correlated with neuroticism and extraversion subscales and pre‐hospitalization suicide/self‐harm behaviours. Results: The bifactor model rendered superior fit to sample data and a robust general factor – accounting for 77.61% of common item variance – providing the first evidence for a tripartite structure of depression and anxiety among adult inpatients. The bifactor solution‐outputted independent general distress, depression, and anxiety factors positively correlated with neuroticism, the personality dimension corresponding to trait negative affectivity. The general distress and depression factors associated with recent self‐harm, but factors showed no associations with prior suicidal behaviour. Conclusions: In adult psychiatric inpatients, general distress substantially underlies comorbid depression and anxiety symptom variation and may contribute to recent incidence of self‐harm. Transdiagnostic assessments and interventions targeting general distress may temper depression, anxiety, and self‐harm in adult inpatients. Practitioner points: Clinical implications Depression–anxiety comorbidity symptomology in adult psychiatric inpatients is primarily composed of general distress. General distress and specific depression are associated with recent self‐harm but not suicidal behaviour. Assessing and treating general distress rather than depression or anxiety specifically may best mitigate comorbid depression and anxiety, and reduce self‐harm behaviour in this clinical population. Cautions and limitations The large sample lacked ethnocultural diversity, and data were cross‐sectional. The use of brief self‐report measures to assess depression and anxiety may have reduced measurement range.